2004
DOI: 10.1099/mic.0.26824-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic analyses of new classes of inhibitors of two-component signal transduction systems using a coupled assay containing HpkA–DrrA from Thermotoga maritima

Abstract: Two-component signal transduction systems (TCSs) play fundamental roles in bacterial survival and pathogenesis and have been proposed as targets for the development of novel classes of antibiotics. A new coupled assay was developed and applied to analyse the kinetic mechanisms of three new kinds of inhibitors of TCS function. The assay exploits the biochemical properties of the cognate HpkA-DrrA histidine kinase-response regulator pair from Thermotoga maritima and allows multiple turnovers of HpkA, linear form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
(66 reference statements)
1
31
0
7
Order By: Relevance
“…6A), Histidine kinases have long been considered attractive targets for the development of new antimicrobial drugs (Macielag and Goldschmidt, 2000;Matsushita and Janda, 2002;Hubbard et al, 2003;Lyon and Muir, 2003;Stephenson and Hoch, 2004;Rowland and King, 2007). Specific inhibitors of histidine kinases have recently been reported based on lead compounds that were identified by high-throughput screening of chemical libraries or from the rational design of compounds (Lyon et al, 2000;Besant et al, 2002;Foster et al, 2004;Gilmour et al, 2005;Qin et al, 2006;Okada et al, 2007). The surface that we have identified as being important for Sda and KipI to inhibit KinA may prove useful as a new target for the rational design of compounds that bind and inhibit histidine kinases.…”
Section: Discussionmentioning
confidence: 99%
“…6A), Histidine kinases have long been considered attractive targets for the development of new antimicrobial drugs (Macielag and Goldschmidt, 2000;Matsushita and Janda, 2002;Hubbard et al, 2003;Lyon and Muir, 2003;Stephenson and Hoch, 2004;Rowland and King, 2007). Specific inhibitors of histidine kinases have recently been reported based on lead compounds that were identified by high-throughput screening of chemical libraries or from the rational design of compounds (Lyon et al, 2000;Besant et al, 2002;Foster et al, 2004;Gilmour et al, 2005;Qin et al, 2006;Okada et al, 2007). The surface that we have identified as being important for Sda and KipI to inhibit KinA may prove useful as a new target for the rational design of compounds that bind and inhibit histidine kinases.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-percent inhibitory concentration (IC 50 ) determinations performed by methods described previously (12) showed that TEP competes with ATP in the coupled assay (Fig. 2).…”
mentioning
confidence: 99%
“…The coupled assay measures the formation of phosphorylated DrrA (Drr-P) in reaction mixtures containing catalytic amounts of HpkA and excess amounts of ATP and DrrA, which are treated as substrates in the kinetic analyses ( Fig. 2 and 3) (12). In the high-throughput screens, we used a filter format of the coupled assay, as described previously (12), which employs 96-well Immobilon P filter plates (Millipore, Inc.).…”
mentioning
confidence: 99%
See 2 more Smart Citations